Using Role Play to Improve Speaking Skills in an ESP class of Medical Laboratory Technology Program - Erlinna Juita (Journal of English Development, 2026)
In Indonesia, English is a foreign language. Therefore, it becomes a compulsory subject taught at schools since Junior High School. In higher education, English is mostly focused on specific purposes rather than general English. Speaking is one of the basic language skills to be improved in the ESP class. However, the students’ performance was still low. Role-play can become one of the alternatives in ESP class to address the challenge. This was classroom action research (CAR) conducted in two cycles in eight weeks. The subjects of this study were selected using the purposive sampling technique. There were 65 fourth-semester students taking the ESP class becoming the participants. The results of the study indicated that the average of students’ performance rose from 2.38 to 3.30 indicating that the students shifted from limited working proficiency to general proficiency which enabled them to use language appropriately in both personal and professional purposes. In conclusion, role-play technique could improve the students’ speaking skills significantly.